Infra-orbital Hyper-pigmentation (Dark Circles) A Study of its Prevalence, Etiology and its Association with Other Dermatological Symptoms among Young Adults - Syed Bilal Ahmed, Sajida Jabeen (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Nowadays, dark circles are among the most important issues facing society. Understanding dark circles is crucial for managing them since they give the eyes a worn-out, aged, and sad appearance. Objective: The objective of this study was to determine the Prevalence of dark Circles its Etiology and its Association with Other dermatological symptoms among young Adults. Material and method: The current cross-sectional study was carried out at PGMIQ/ BMC Hospital Quetta from November 2022 to April 2023 after taking permission from the ethical board of the institute. The research was carried out on the college students. Participants between the ages of 17 and 25 who provided informed consent were included in the study. A Questionnaire was shared among the participants which had three sub-sections, demographic data, perceived psychological stress, and dermatological questions, Questionnaire on Perceived Stress Scale (PSSQ).Version 24 of SPSS was used to evaluate the data. The standard deviation and mean are used to tabulate all statistical data. Statistical significance is defined as a P-value of less than 0.05 (P = < 0.05). Results: A total of 375 individuals were included in this study out of which females were 285(76%) and males were 24%. Among the study participants the prevalence of Infra-orbital- hyper-pigmentation was 300(80%). We assessed a lot of habits that were related to the rate of infra-orbital hyperpigmentation and showed that using cosmetics, sunscreen, face wash, and having a lot of psychological stress, were all substantially correlated with the degree of dark circle. On the other hand, the amount of infra-orbital hyperpigmentation was independent to daily sun exposure, sleep duration, eye cream use, smoking, fluid intake, and face therapies. We used the SSCQ (self-reported skin complaint questionnaire) to assess various dermatological skin issues and correlate the degree of IOHP with them. The two most common skin conditions among the individuals were acne or pimples (65%) and oily skin (70%).Oily skin, & pimples / acne (p = 0.005) were shown to be significantly correlated. Conclusion: The current study concluded that the prevalence of infraorbital orbital hyperpigmentation is high among adults. Various factors, including the use of face wash, sunscreen, cosmetics, high psychological stress, and certain dermatological factors like oily skin and acne, were found to be significantly associated to it prevalence. Keyword: Infra-orbital Hyper-pigmentation; Dark Circles; Prevalence; Etiology; Young Adults